Development Strategy of Potential Non-Timber Forest Product Commodities in the Boti Indigenous Community, Indonesia - Dako, Fransiskus Xaverius; Setyowati, Retno; Herningtyas, Wieke; Pujiono, Eko; Budiman, Imam; Oskar Krisantus, Oematan; Paga, Blasius (Jurnal Manajemen Hutan Tropika, 2024)
The Boti indigenous community on Timor Island utilizes non-timber forest products for their daily lives, but there is a lack of information about their potential and sustainable use, which requires an empowerment initiative for them. This study aims to investigate the potential and utilization of NTFPs while also formulating an NTFPs development strategy in Boti Village. A combined method, including literature review, plot measurement, socio-economic surveys, and interviews, was used to collect data. NTFPs were evaluated for their potential using the importance value index; their utilization was studied through an ethnobotanical survey; and an NTFP development strategy was formulated utilizing a SWOT-PESTLE analysis. The results show that three types—candlenut, tamarind, and lac tree—dominate among the 13 species of the NTFPs. NTFPs are used for various purposes, such as medicinal, natural dye weaving, and selling to raise household income. The NTFPs development in Boti village needs to be prioritized, with a focus on increasing the added value of NTFPs through funding, facilitation, technological assistance, planting and preserving, collaborating more, and enforcing formal and customary rules. The results can be used as a baseline or reference for sustainable NTFP management and the empowerment of the Boti indigenous community.